An analytical wall-function for turbulent flows and heat transfer over rough walls - Suga, K.; Craft, T.J.; Iacovides, H. (The International journal of heat and fluid flow, 2006)
This paper reports the development of a refined wall-function strategy for the modelling of turbulent forced convection heat transfer over smooth and rough surfaces. In order to include the effects of fine-grain surface roughness, the present study extends a more fundamental work by Craft et al. [Craft, T.J., Gerasimov, A.V., Iacovides, H., Launder, B.E., 2002. Progress in the generalisation of wall-function treatment. Int. J. Heat Fluid Flow 23, 148–160] on the development of advanced wall-functions of general applicability. The presently proposed model is validated through comparisons with data available for internal flows through channels and for external flows over flat and curved plates with both smooth and rough surfaces. Then, its further validation in separating flows over a sand dune and a sand-roughened ramp is discussed. The validation results suggest that the presently proposed form can be successfully applied to a wide range of attached and separated turbulent flows with heat transfer over smooth and fine-grain rough surfaces.